Diagnostic Accuracy of Serologic (IGG) in Diagnosis of Helicobacter Pylori among Patients of Dyspepsia by Taking Stool Antigen (HPSA) as Gold Standard - Ishtiaque Ahmed Memon, Mukesh Kumar, Kheemchand, Farhina Nasir, Suhrab Khan Talpur, Damni Advani, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the diagnostic accuracy of serologic (IgG) in the diagnosis of Helicobacter Pylori among patients of dyspepsia by taking Helicobacter pylori Stool Antigen (HpSA) as the gold standard. Material and methods: The study was conducted in Microbiology Department, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi with the collaboration of gastroenterology OPD. All the patients with a history of dyspepsia, above 25 years of age and of either gender were included. After taking informed consent the clinical samples of blood and stool from patients were taken. A 6 ml venous blood was taken from the antecubital vein for detecting IgG antibody to H. pylori. Stool samples were collected for detecting H. pylori antigen in a wide mouth, sterile, leak proof container properly labeled by serial number and stool samples were stored in a refrigerator at 4°C up to 72h. On the specimens containing H. pylori antibodies, a colored line appeared in the test line region consider a positive result. H. pylori antigen was detected in stool (HpSA) by rapid chromatographic immunoassay. During analysis, the specimen responds with an anti-H. pylori antibody-coated particle. By capillary action, the mixture migrates upward on the membrane, reacting with anti-H. pylori antibodies on the membrane to produce a colorful line. A positive result is indicated by the presence of this colored line in the test zone, whereas a negative result is indicated by its absence. All the data were obtained using a study proforma, and the data was analyzed using SPSS version 26. Results: A total of 210 patients presented with dyspepsia were studied, their mean age was 49.07±10.97 and females were in majority (71.9%). H. Pylori was positive among 137 cases, those who underwent serological test (IgG) and 127 were positive for stool antigen (HpSA). The diagnostic accuracy of serological test (IgG) was found 95.23% by taking Stool Antigen (HpSA) test gold standard followed by sensitivity 92.7%, specificity 100%, PPV 100% and NPV 87.95%. Conclusion: The diagnostic accuracy of serological test (IgG) was found 95.23% by taking Stool Antigen (HpSA) test gold standard followed by sensitivity 92.7%, specificity 100%, PPV 100% and NPV 87.95%.